1996
DOI: 10.1007/s002040050364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the toxicity of allyl alcohol, coumarin and menadione in precision-cut rat, guinea-pig, Cynomolgus monkey and human liver slices

Abstract: The toxicity of allyl alcohol, coumarin and menadione has been studied in precision-cut liver slice cultures. Liver slices were prepared from male Sprague-Dawley rats, male Dunkin-Hartley guinea-pigs and from samples of Cynomolgus monkey and human liver using a Krumdieck tissue slicer. The liver slices were cultured with the test compounds for 24 h in a dynamic organ culture system. Toxicity was assessed by measurement of protein synthesis, potassium content and the MTT assay. At the concentrations examined, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In fact, a previous study demonstrated that although both human livers and rat livers are damaged by AA, the latter was less susceptible to AA-induced toxicity than the former. 48 Elucidation of these possibilities is a pivotal task to improve the low differentiation efficiency. The ultimate goal of differentiation studies is the amendment of damaged tissue by cellular transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a previous study demonstrated that although both human livers and rat livers are damaged by AA, the latter was less susceptible to AA-induced toxicity than the former. 48 Elucidation of these possibilities is a pivotal task to improve the low differentiation efficiency. The ultimate goal of differentiation studies is the amendment of damaged tissue by cellular transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…With this shortcoming in mind, both matrices are still useful tools to assess hepatic f m(AO) , using known specific AO inhibitors. Both raloxifene and menadione are potent uncompetitive inhibitors (Johns, 1967;Obach, 2004;Obach et al, 2004), however, neither is appropriate for use in determining f m(AO) in hepatocytes or S9 fractions because of one or a number of the following: 1) P450 inactivation (Pearson et al, 2007), 2) P450 reversible inhibition (Floreani and Carpenedo, 1990), and/or 3) cytotoxic effects (Price et al, 1996). Recently, Strelevitz and colleagues (2012) provided information on hydralazine as a selective inhibitor of aldehyde oxidase in human hepatocytes, and their work supports hydralazine having the appropriate inhibitory attributes to be used to determine f m(AO) for compounds.…”
Section: In Vitro Considerations To Assess Aldehyde Oxidase Metabolismmentioning
confidence: 99%
“…Oasis HLB can be used within a wide range of pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and this was used for optimisation. For pH 1-2 the signal from Vitamin E decreased.…”
Section: Optimisation Of the Solid-phase Extraction Systemmentioning
confidence: 99%
“…These vitamins are regarded as useful clinical indicators of the incidence of cancer, myocardial infarction, haemorrhage and osteomalacia diseases. The toxicity of fat-soluble vitamins has been studied in precision-cut liver-slice cultures [2,3]. Over the last decade, nutritionists and clinicians have been increasingly interested in measuring these fat-soluble vitamins in human plasma in order to evaluate their status, fat malabsorption disorders or their toxic levels.…”
Section: Introductionmentioning
confidence: 99%